Beyond Violence : Religious Sources of Social Transformation in Judaism, Christianity, and Islam - Heft, James (Book collections on Project MUSE., 2004)
In an age of terrorism and other forms of violence committed in the name of religion, how can religion become a vehicle for peace, justice, and reconciliation? And in a world of bitter conflicts-many rooted in religious difference-how can communities of faith understand one another?The essays in this important book take bold steps forward to answering these questions. The fruit of a historic conference of Jewish, Christian, and Muslim scholars and community leaders, the essays address a fundamental question: how the three monotheistic traditions can provide the resources needed in the work of.